A study on the sustainability of marriage among community in Seremban, Negeri Sembilan, Malaysia / Amira Omar, Mohd Ramlan Mohd Arshad and Farhana Sahir - Omar, Amira; Mohd Arshad, Ramlan; Sahir, Farhana (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
The aim of this study is to explore the antecedents for sustainability of marriage among community with the main objectives of exploring the relationship between the variables namely loyalty and faithful, compromise and tolerance, financial stability and intimate relationship towards sustainability of marriage and derive the main factor that affect the prolong marriage and relationship. 200 respondents of this study are community lived in Seremban, Negeri Sembilan. Purposive sampling technique was used with questionnaire as the instrument. Correlation and regression analysis was conducted, and the findings show that there is a significant relationship between the variables and sustainability of marriage with financial stability as the main factor. Hence, various parties such as authority, non-governmental bodies and community has benefited from the study.